ASPEK PEMBELAJARAN DARI KESENIAN BARONGAN BAGI MASYARAKAT DESA BEJIREJO - Siti Layinatul Halimah; Atiqa Sabardila (Universitas PGRI Adi Buana Surabaya, 2023)
This article has the following objectives: (1) to know the values ​​contained in barongan art, (2). Analyzing the performance structure in barongan art, (3). Describe the function of barongan in traditional traditions. This study uses the method of observation, interviews, and document study. Observations were made openly at the house of the head of the barongan art group Harjuno Mudo. The research results are (1). Various aspects that can be used as daily learning are spiritual values, moral values, and social values, (2). The structure of the Barongan performance often changes in each performance, (3). The Barongan performance is an earth charity ritual with supporting components and a presentation arrangement that is different from the Barongan performance in general. The form of barongan art performances is divided into two, namely processions that contain spiritual values ​​and dramas that contain social values. There are two forms of presentation of barongan related to its function, namely the form of parade and dance drama.